Prevalence of Dental Fear and Anxiety and its Association with Behavior Using Three Fear and Anxiety Measurement Scales among Children in Faridabad - Tanya Kakkar; Bhavna G Saraf; Gauri Kalra; Neha Sheoran; Anam K Khan; Pallavi Lakhanpal (Journal of South Asian Association of Pediatric Dentistry)
Introduction: Dental fear and anxiety (DFA) start mostly at the beginning of childhood and persist through adolescence, and it can have a major influence toward the provision of dental services. For effective dental treatment, a good rapport between the pedodontist and the patient is the key, which helps in identifying anxious children. Aim: The aim of the study was to assess the prevalence of DFA and its association with behavior, using three fear and anxiety measurement scales among children in Faridabad. Materials and methods: A cross-sectional study was conducted on 400 children (3–14 years) who visited the Department of Pedodontics and Preventive Dentistry. The children were divided into three groups according to age, and DFA levels were assessed by three sets of questionnaires, namely: Modified Child Dental Anxiety Scale (MCDAS) faces version, Children's Fear Survey Schedule-Dental Subscale (CFSS-DS), and Dental Fear Survey (DFS). The operator assessed the behavior of the children according to modified Frankl's behavior rating scale (MFBRS). Results: The prevalence of high dental fear in children aged 3–14 years was 63.8% according to MCDAS, 50.8% according to DFS, and 54% according to CFSS-DS. In the assessment of the impact of age on dental fear levels, it was found that the level of DFA decreases with an increase in age. Conclusion: Assessment of DFA, along with behavior management, is the most vital tool in the hands of pediatric dentists, as it helps them to execute the required treatment plan in the most effective manner.